Strategi Peningkatan Usaha Mikro, Kecil, dan Menengah di Era Digital - Firdaus, Lukman; Amelia, Resti; Hakim, Lukman (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2024)
Indonesia is a country with very abundant natural resources. This can make Indonesia a country with the largest economy in the world. However, Indonesia still has social problems, namely poverty and unemployment. This research aims to explain this problem through empowerment, especially through improving micro, small, and medium enterprises (SMEs). This research method uses descriptive qualitative with a literature study approach supported by secondary data. The results of this research, viewed from an economic aspect, state that the existence of SMEs has an important role in improving the Indonesian economy, especially in the formation of Gross Domestic Product (GDP) and community welfare. The higher the level of social welfare, the higher the country's economic development and growth. For this reason, a strategy is needed to improve MSMEs, one of which is by utilizing advances in digital technology through e-commerce and social media. The government's role is to improve digital infrastructure so that internet access speed can be evenly distributed. Indonesia merupakan salah satu negara dengan kekayaan sumber daya alam yang sangat melimpah. Hal ini dapat menjadikan Indonesia sebagai negara dengan ekonomi skala besar di dunia. Akan tetapi, Indonesia masih memiliki kendala pada permasalahan sosial yaitu kemiskinan dan pengangguran. Tujuan adanya penelitian ini adalah untuk menguraikan masalah tersebut melalui pemberdayaan, khususnya melalui peningkatan terhadap usaha mikro, kecil, dan menengah (UMKM). Metode penelitian ini menggunakan deskriptif kualitatif dengan pendekatan studi pustaka yang didukung oleh data-data sekunder. UMKM memiliki peran penting dalam meningkatkan perekonomian Indonesia, terutama terhadap pembentukan Produk Domestik Bruto (PDB) dan kesejahteraan masyarakat. Untuk itu, UMKM perlu dikembangkan salah satunya dengan memanfaatkan kemajuan teknologi digital melalui e-commerce dan media sosial. Peran pemerintah juga sangat dibutuhkan dalam meningkatkan infrastruktur digital agar kecepatan akses internet dapat merata.